Pseudomonas aeruginosa invasion of and multiplication within corneal epithelial cells in vitro. - Fleiszig, S M (1995)
Pseudomonas aeruginosa is usually considered an extracellular pathogen. Using assays to determine intracellular survival in the presence of gentamicin, we have previously demonstrated that P. aeruginosa is able to invade corneal cells during infectious keratitis in mice. In vitro, P. aeruginosa was found to enter the following cells: human corneal cells removed by irrigation; epithelial cells in the cornea of rats, mice, and rabbits; and primary corneal epithelial cells cultured from rat and rabbit eyes. The level of invasion was related to the level of adherent or associated bacteria. In general, invasion was more efficient with cultured epithelial cells than with cells tested in situ. Invasion did not occur when assays were performed at 4 degrees C. Cytochalasin D but not colchicine inhibited bacterial invasion, suggesting that bacterial entry was an endocytic process dependent on actin microfilaments but not microtubules. Bacteria that invaded cultured corneal epithelial cells were found to multiply within cells. The ability of P. aeruginosa to invade and multiply within corneal epithelial cells may contribute to the virulence of this organism during infectious keratitis, since intracellular bacteria can evade host immune effectors and antibiotics commonly used to treat infection.